(untitled) (Applied Biological Research, 2011)
Extremely low frequency electromagnetic fields (EMFs) produce both positive and negative effects on biological processes and the present study was aimed to evaluate the effect of low frequency EMF on some biochemical parameters in rats. Forty five rats in 3 groups viz., control group (kept under normal conditions in animal room), group 2 (exposed for 135 days and under 50 Hz, 1 mT emitted from solenoid for 24 h daily), and group 3 (sham group kept under conditions similar to group 2, except in off solenoid). Blood samples were collected to determine the concentration of cortisol, glucose, cholesterol and triglycerides in plasma. In EMF exposed group plasma levels of cortisol, glucose, cholesterol and triglyceride were significantly lower than those of other groups revealing that long term exposure to EMF has potential clinical use with no immunosuppressive effect.